Mexiletine Treatment for Neonatal LQT3 Syndrome: Case Report and Literature Review - Bagkaki, Alena; Tsoutsinos, Alexandros; Hatzidaki, Eleftheria; Tzatzarakis, Manolis; Parthenakis, Fragiskos; Germanakis, Ioannis (Frontiers in Pediatrics, 2021)
Background: Early diagnosis of long QT type 3 (LQT3) syndrome during the neonatal period is of paramount clinical importance. LQT3 syndrome results in increased mortality and a mutation-specific response to treatment compared to other more common types of LQT syndrome. Mexiletine, a sodium channel blocker, demonstrates a mutation-specific QTc shortening effect in LQT3 syndrome patients. Case Presentation: A neonate manifested marked QTc prolongation after birth. An electrocardiogram (ECG) recording was performed due to positive family history of genetically confirmed LQT3 syndrome (SCN5A gene missense mutation Tyr1795Cys), and an association with sudden cardiac death was found in family members. The mexiletine QTc normalizing effect (QTc shortening from 537 to 443 ms), practical issues related to oral mexiletine treatment of our young patient, along with a literature review regarding identification and mexiletine treatment in infants with LQT3 syndrome are presented. Conclusions: Mexiletine could be considered in the treatment of high-risk LQT3 patients already in the neonatal period in addition to b-blocker therapy. Availability of standardized commercial mexiletine pediatric formulas, serum mexiletine level analyses, and future prospective studies are needed to evaluate the potential beneficial effect of early mexiletine treatment on the incidence of future acute cardiac events in these high-risk LQT syndrome patients.